4a+5b-2(b+a)=

Simple and best practice solution for 4a+5b-2(b+a)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a+5b-2(b+a)= equation:


Simplifying
4a + 5b + -2(b + a) = 0

Reorder the terms:
4a + 5b + -2(a + b) = 0
4a + 5b + (a * -2 + b * -2) = 0
4a + 5b + (-2a + -2b) = 0

Reorder the terms:
4a + -2a + 5b + -2b = 0

Combine like terms: 4a + -2a = 2a
2a + 5b + -2b = 0

Combine like terms: 5b + -2b = 3b
2a + 3b = 0

Solving
2a + 3b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3b' to each side of the equation.
2a + 3b + -3b = 0 + -3b

Combine like terms: 3b + -3b = 0
2a + 0 = 0 + -3b
2a = 0 + -3b
Remove the zero:
2a = -3b

Divide each side by '2'.
a = -1.5b

Simplifying
a = -1.5b

See similar equations:

| .83X=5 | | 16=2/3(10x+12) | | 16=1.5(7x+6) | | 3=1/3(10x+3) | | 13=.8(x+20) | | 1=2.5(5x+8) | | (48-2x)(62-2x)=0 | | v^-3/v^-6 | | -8x-6=-2x-60 | | -n=1/3^-5 | | (x^2-4x-2)x(x+7)= | | 3(2p+3q)+-4q= | | -7x-6=-12x-41 | | -n=1/4^-4 | | (x^2-4x-2)(x+7)= | | -n=1/9^-2 | | -14x+6=-6x+38 | | -14x+6=-6+38 | | 3x-2=-4x+33 | | 17x-2=8x+88 | | -n=1/5^-5 | | 9y-1=-10+12y | | -5(7n-4)+3= | | 2y-14=4y+4 | | P=2(26)+2(91) | | 5y+6y-81=7y+102+65 | | 3t^4=8t | | x+x+125000=550000000 | | 12x+8y-12=0 | | 4*x-9/2+12=0 | | 51x^2-5x-4= | | x+x+4=238 |

Equations solver categories